Amplifying Voices: Engaging and Disengaging with Colonial Pasts in Amsterdam. (3rd May 2020) - Ariese, Csilla E.
ABSTRACT: As the metropole and main harbor city of a colonial, maritime empire, much of Amsterdam's development has been the direct or indirect result of colonial activities. Yet, many aspects of colonialism and its lasting entanglements were not (widely) spoken about. In response, within the cultural sphere, de-colonial engagements have arisen across various institutions and related to multiple aspects of colonialism, most prominently the topic of slavery. This paper identifies and analyzes recent examples of such de-colonial engagements – e.g., the exhibition Afterlives of Slavery, the installation Blood Sugar, and the publication Words Matter – which have created or amplified conversations about colonial pasts. It seeks to show that artists and activists are often the initiators of these challenges to existing paradigms and perspectives, but that afterwards these voices are amplified by cultural and scientific institutions, before resonating within the public sphere. The recent (2019) controversy surrounding the use of the term "Golden Age" is a case in point. Yet, despite these amplifying de-colonial conversations, there are still significant silences and absences, revealing the borders of tolerance in terms of dealing with colonialism in the contemporary. The intention is therefore also to understand how these voices are not only amplified but also potentially altered or even limited as they move from activist arenas, through cultural institutions, into the wider public eye.